Penerapan Film Pendek Edukasi dalam Meningkatkan EMC2 (Empathy, Compassion, Mindfulness, and Critical Inquiry) di SDN 105327 - Barus, Lailan Safitri; Sujarwo, Sujarwo; Rosadi, Mimi; Tampubolon, Lasni Roha (Invention: Journal Research and Education Studies, 2025)
This study aims to examine the effectiveness of using educational short films in enhancing EMC² competencies (Empathy, Compassion, Mindfulness, and Critical Inquiry) among fifth-grade students at SDN 105327 Pedamean. The research employed a Classroom Action Research (CAR) approach carried out in three cycles, each consisting of planning, action, observation, and reflection stages. Data collection instruments included observation sheets, interview guidelines, and student reflection sheets. The results indicated a gradual improvement in EMC² competencies across the cycles. In the first cycle, students showed basic emotional responses but struggled to express meaningful reflections. The second cycle demonstrated increased empathy and compassion through group discussions and roleplay, while the third cycle showed significant growth in mindfulness and critical inquiry through mini debates and reflective journaling. Despite some challenges, such as varied individual responses and verbal participation barriers, educational short films proved effective in fostering students' social-emotional skills. This study recommends integrating short films as a creative and contextual strategy for character education in elementary schools.